Role of DNA Methyltransferases in the Epigenome - Jeltsch, Albert (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
DNA methylation, a modification found in most species, regulates chromatin functions in conjunction with other epigenome modifications, such as histone post-translational modifications and non-coding RNAs. In mammals, DNA methylation has an essential role in development by orchestrating the generation and maintenance of the phenotypic diversity of human cell types. Recent years have brought spectacular advances in our understanding of the mechanism, function and regulation of DNA methyltransferases through their interaction with other epigenome modifications, chromatin factors and post-translational modifications, which are described in this Special Issue of Genes. Manuscripts are specifically addressing describing the targeting and regulation of DNA methyltransferases by interacting factors and their roles in cellular differentiation and the development of diseases. Prof. Dr. Albert Jeltsch and Prof. Dr. Humaira Gowher, Guest Editors